2010
DOI: 10.1074/jbc.m109.064618
|View full text |Cite
|
Sign up to set email alerts
|

Gentisic Acid, a Compound Associated with Plant Defense and a Metabolite of Aspirin, Heads a New Class of in Vivo Fibroblast Growth Factor Inhibitors

Abstract: Fibroblast growth factors are key proteins in many intercellular signaling networks. They normally remain attached to the extracellular matrix, which confers on them a considerable stability. The unrestrained accumulation of fibroblast growth factors in the extracellular milieu, either due to uncontrolled synthesis or enzymatic release, contributes to the pathology of many diseases. Consequently, the neutralization of improperly mobilized fibroblast growth factors is of clear therapeutic interest. In pursuing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 88 publications
8
106
0
Order By: Relevance
“…These data are in accordance with clinical studies showing that strategies to destroy neovessels (i.e local injection of a sclerosing agent, polidocanol) lead to pain improvement [7]. Etamsylate, an inhibitor of fibroblast growth factor (FGF), when locally applied, supresses FGF-driven angiogenesis [8,9]. Since FGF participates in nociception [10,11], injecting etamsylate into the areas of tendon neovascularization could not only decrease the number of pathologic neovessels, but also eradicate the pain-generation nerve fibres.…”
Section: Discussionsupporting
confidence: 86%
“…These data are in accordance with clinical studies showing that strategies to destroy neovessels (i.e local injection of a sclerosing agent, polidocanol) lead to pain improvement [7]. Etamsylate, an inhibitor of fibroblast growth factor (FGF), when locally applied, supresses FGF-driven angiogenesis [8,9]. Since FGF participates in nociception [10,11], injecting etamsylate into the areas of tendon neovascularization could not only decrease the number of pathologic neovessels, but also eradicate the pain-generation nerve fibres.…”
Section: Discussionsupporting
confidence: 86%
“…It was demonstrated that CaD inhibits microvessel formation through hindering hypoxia-inducible factor-1α and VEGF overexpression, thus, reflecting a reduction in choroidal angiogenesis in the retinas of diabetic animal models [39,40] . Furthermore, dobesilate is an FGF receptor antagonist able to inhibit FGF-induced fibroblast proliferation and also inhibiting neovascularization in mice [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Dobesilate is a powerful inhibitor of FGF that shows a markedly anti-inflammatory, anti-proliferative and anti-angiogenesis activity in several inflammations and angiogenesis-dependent diseases. [12][13][14][15][16] It seems obvious that all these activities may contribute to the clinical improvement of dobesilate in knee arthritic patients. Furthermore, the consequences of inhibition of FGF production by dobesilate are the direct inhibition of cell proliferation and angiogenesis.…”
Section: Case Reportmentioning
confidence: 99%